Salesforce CPQ implementation handbook : configure salesforce CPQ products to close more deals and generate higher revenue for your business - Ramanujan, Madhu (Packt Publishing, 2022)
An end-to-end practical guide to implementing Salesforce CPQ solutions, shortening your sales cycle, and generating a higher ROI Key Features Maximize sales by reducing turnaround time and providing a quick analysis of profits and losses Get up to speed with Salesforce CPQ concepts, best practices, and tips when choosing the right CPQ implementation strategy Implement CPQ configurations and automations for B2B and B2C business scenarios Book Description Salesforce CPQ is innovative software that enables you create better quotes, improve quoting accuracy, and maximize sales and deals. It also provides a quick analysis of profits and losses, helping you improve the overall execution of sales processes, and allows a great deal of flexibility for your prospects, customers, and business partners. The book starts with the Quote-2-Cash business process in Salesforce and shows you how to assess when a business needs to implement CPQ. You'll then progress to configuring opportunities, quotes, and CPQ products. As you advance, you'll understand how to define and configure price books, price rules for CPQ quote automation, multidimensional quoting, and more. Next, you'll look at how to configure CPQ guided selling and create package configurations, contracts, and amendments. Later chapters will demonstrate how to perform data migration from a legacy system and the order in which the objects are to be migrated. You'll also explore CPQ billing and its advantages with the help of different use cases before learning about Industries CPQ and how it is different from standard Salesforce CPQ. Finally, you'll discover best practices for achieving optimal CPQ performance and avoiding performance bottlenecks. By the end of this Salesforce book, you'll be able to implement Salesforce CPQ for any business. What you will learn Understand Quote-2-Cash business processes and configure opportunities and quotes Create custom CPQ actions and use custom filters for automating business needs Discover how to configure products and product rules Understand the CPQ pricing structure and methods, rules, multidimensional quoting, and quote automation Explore the CPQ data model and use the Salesforce Schema Builder to view and configure object relationships Configure contracts, amendments, and renewals in Salesforce Focus on CPQ billing and its advantages Gain comprehensive insights into Industries CPQ Who this book is for This book is for Salesforce administrators, business analysts, functional consultants, sales managers, Salesforce architects, and those looking to gain Salesforce CPQ certification. Working knowledge of the Salesforce ecosystem is recommended to get the most out of this book.